Telegram Application to Monitor and Control of Automatic Railway Crossing Prototype Using Automatic Transfer Switch - Wusandi Janu Ramadhan; Amirullah Amirullah; Asepta Surya Wardhana (Vokasi UNESA Bulletin of Engineering, Technology and Applied Science, 2024)
A railroad crossing is a device that functions to close and open roads that limit or stop public traffic lanes so that vehicles stop temporarily and give priority to trains. Failure of a railroad crossing will have fatal consequences because it will cause accidents and cause fatalities, injuries, or other material losses. The accident occurred because there was no equipment or failure of officers when operating the railroad crossing. To overcome these obstacles, the railroad crossing was made automatically. This paper proposes a prototype control of an automatic railroad crossing using an automatic transfer switch (ATS) monitored by the Telegram application. The main power source of the railroad crossing prototype is a photovoltaic generator system consisting of solar modules, inverters, and batteries. ATS is proposed so that the system is able to automatically transfer the power supply from the solar power generator to PLN electricity if the battery voltage is not enough to drive the railroad crossing or vice versa. The results of the study show that the combination of a 50 Wp solar module and a VRLA battery (12V and 12Ah) is able to store and generate electricity to drive the railroad crossing. The INA219 sensor is able to measure the current, voltage, and power of the PV module and battery. Arduino Uno is able to process voltage and current sensor data, send and receive UART data (RX TX), and communicate with ESP8266. Data from ESP8266 can then be sent and monitored remotely by the Telegram application via Arduino-Uno. The results of DC current and DC voltage tests using the INA219 sensor between the Telegram application and Multimeter are able to produce errors below 5%. The Telegram application is also able to monitor the DC voltage and DC current of PV modules and batteries, as well as the DC adapter voltage and DC adapter current from PLN remotely, and the status of opening and closing the railway crossing gate based on the power supply selection by ATS.